18F-fluorodeoxyglucose positron emission tomography/computed tomography findings in descending necrotizing mediastinitis and cervical vertebral osteomyelitis in a cancer patient: A case report. Issue 30 (24th July 2020) - Yoo, Jin Young; Yoo, Min Young; Lee, Ki Hyeong; Koong, Sung-Soo
Abstract: Rationale: A deep neck infection (DNI) with descending necrotizing mediastinitis (DNM) has great clinical importance because of its high morbidity and mortality, particularly when associated with predisposing underlying disease. With the expanding clinical use of 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), it may be necessary to perform FDG PET/CT for immediate diagnosis and treatment of DNM. To the best of our knowledge, this is the first case report of DNI with DNM diagnosed based on FDG PET/CT findings. Patient concerns: A 65-year-old man who underwent chemotherapy for stage IV lung cancer complained of sore throat, fever, and mild pain in the right upper arm for 4 days before admission. Diagnoses: FDG PET/CT revealed retropharyngeal abscess with acute osteomyelitis of the vertebral bodies of C4 and C5 and DNM. In blood and sputum cultures, Klebsiella pneumoniae was isolated. DNI with DNM was diagnosed based on contrast-enhanced neck and chest CT. Interventions and outcome: Because of his underlying condition, antibiotic therapy with ceftriaxone and ciprofloxacin was started. There was initial improvement, but the patient died after 2 weeks from sepsis and multiorgan failure. Lessons: The findings of DNI with DNM on FDG PET/CT were as follows: as an acute infection, DNM showed more severe uptake relative to the average maximum standardized uptake value of brown fat or physiologic muscle; showed the prevertebral uptake pattern rather than the paravertebral uptake pattern of brown fat; and showed continuous patterns of hypermetabolic lesions from the retropharyngeal/parapharyngeal space to the thoracic prevertebral space.